Gas chromatography/time-of-flight mass spectrometry for identification of compounds from parkia speciosa seeds extracted by Supercritical Carbon Dioxide - Z., Salman; C. Y., Mohd. Azizi; N. A., Nik Norulaini; A. K., Mohd. Omar (2006)
Parkia speciosa seeds chemical constituents that were obtained from Supercritical Carbon Dioxide (SC-CO2) extractions were analysed by Gas Chromatography-Time of Flight Mass Spectrometry (GC/TOF-MS). The SC-CO2 extraction was conducted at the interaction temperature and pressure of; 313 K/20.68 MPa; 353 K/20.68 MPa; 313 K/55.16 MPa and 353 K/ 55.16 MPa in the regime of 50 minutes extraction time. The analysis of compound was based on percentage of similarity and peak area of more than 75% and 0.1% respectively. Propanoic acid, 3, 3'-thiobis - didodecyl ester was present with highest percentage area in most sample condition. Other main compounds were linoleic acid chloride, palmitic acid, linoleic acid, myristic acid, arachidonic acid, undecanoic acid and 2-Hexyl-1-decanol. Terpenoids compounds of ÃŸ-sitosterol and squalene were identified at all conditions, while some other compounds such as stigmasterol, lupeol and campesterol were identified only at certain condition. The analysis found 77 compounds in all of the extracted samples. The combination in chromatographic separation with an identification technique as in GC/TOFMS has made it possible to detect the variability obtained by different SC-CO2 extraction condition and separation of different chemical compounds in Parkia speciosa seeds.